A design methodology for an EM wave absorber with a sub-skin depth periodic pattern using Ni deposition. (2nd January 2023) - Baek, Sang Min; Lee, Won Jun; Kim, Sangyong; Go, Jeongin; Lee, Jongkwang
Abstract : An electromagnetic (EM) wave absorber using a periodic patterned layer is one approach to absorb harmful EM waves. In this approach, radar absorption performance is defined by the impedance characteristics from the pattern configuration, resistance, and properties of the substrate surrounding the pattern. Generally, a metal tends to reflect incident EM waves, but they can also have resistive characteristics for thicknesses of the material less than the skin depth. In this study, a periodic patterned layer was proposed with an ultra-thin layer of metallic particles using physical vapor deposition. The properties of the deposited layer for several metal types were studied; Ni was selected for the proposed layer for the patterned EM wave absorber based on its sheet resistance and low standard deviation. The sheet resistance of Ni was controlled by the deposition time, with a sheet resistance of 53 and 35 Ω/sq attained at deposition times of 4 and 9 s, respectively. The pattern configuration was designed and fabricated with consideration of the design frequency. The absorption characteristics were estimated by unit cell simulation and also measured in free space. The designed absorber exhibited a minimum reflection loss at 12 GHz. This work suggests the feasibility of a periodic patterned wave absorber made using a pure metallic layer.